AGULHAS Atlas (Computer Diskette). - WOODS HOLE OCEANOGRAPHIC INSTITUTION MA (1990)
File characteristics: Computer data and program (7 computer files); ASCII character set. Physical description: 1 computer disk; 3 1/2 in.; 1.2m. System requirements: IBM compatible; MS-DOS 3.3 or higher; microsoft quick basic; color monitor preferred. This is a floppy disk on which can be found the one-day average currents, the path of the Agulhas Current, CTD stations in 'Live Atlas' format, SST frontal analyses (Chassignet and Olson, personal communication) as well as programs written in QuickBASIC which allow one to access and display these observations. The programs are stored in ASCII and can be run under the Microsoft QuickBasic (Version 4.0 or higher). Instructions for running the programs can be found in a file entitled 'read.me' on the disk. Includes documentation, AD-A237 209. Sponsored in part by Contract N00014-85-C-0001. Manual on disk, but not figures which are in manual.